2019
DOI: 10.1158/0008-5472.can-18-2383
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Deficiency Confers Apoptosome and Mitochondrial Dysfunction in African-American Men with Prostate Cancer

Abstract: Although African-American (AA) patients with prostate cancer tend to develop greater therapeutic resistance and faster prostate cancer recurrence compared with Caucasian-American (CA) men, the molecular mechanisms of this racial prostate cancer disparity remain undefined. In this study, we provide the first comprehensive evidence that cytochrome c deficiency in AA primary tumors and cancer cells abrogates apoptosome-mediated caspase activation and contributes to mitochondrial dysfunction, thereby promoting the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Furthermore, Cytc was lower expressed in BC compared with benign breast lesions and low expression of Cytc was correlated with higher histological grade, ER status, PR status and recurrence. A similar correlation was found in prostate cancer which Cytc de ciency contributed to tumor invasiveness and faster recurrence [27]. Importantly, we also found that decreased expression of Cytc was an independent prognostic factor in breast cancer solid tumors and played a pivotal role in the poorer 5-DFS of that cohort of BC patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, Cytc was lower expressed in BC compared with benign breast lesions and low expression of Cytc was correlated with higher histological grade, ER status, PR status and recurrence. A similar correlation was found in prostate cancer which Cytc de ciency contributed to tumor invasiveness and faster recurrence [27]. Importantly, we also found that decreased expression of Cytc was an independent prognostic factor in breast cancer solid tumors and played a pivotal role in the poorer 5-DFS of that cohort of BC patients.…”
Section: Discussionsupporting
confidence: 87%
“…Jamsheed [26] et al demonstrated that in non-small cell lung cancer patients, Cytc level was lower than healthy individuals, and the lower expression of Cytc were associated with advanced stages, high grade histological differentiation and shorter overall survival. Rahul [27] et al explored that in prostate cancer, Cytc de ciency contributed to tumor invasiveness and therapeutic resistance, and leaded to faster recurrence. It has been widely reported that VDAC1 participates in the release of Cytc, which is able to signal Cytc to initiate the mitochondrial-mediated cell death cascade [28].…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture of Lewis Lung carcinoma for tumor implant: LLC cells (ATCC CRL-1642) were cultured in High-Glucose Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and 1% Penicillin/Streptomycin/Amphotericin (PSA) to confluency, and these were gently scraped off the plate, pelleted, quantified. To induce a tumor, mice were subcutaneously injected 1x10 7 LLC cells in a 400µL total volume composed of 200µL ECM Growth factor reduced gel from Engelbreth-Holm-Swarm murine sarcoma (SIGMA), and 200µL cell suspension in media into the upper right dorsal area of their body.…”
Section: Cell Growth and Induction Of Lewis Lung Carcinoma In Micementioning
confidence: 99%
“…Cytochrome c (Cyt c) release is one key event of the mitochondrial apoptotic pathway that triggers the caspase activation cascade [6]. It has been shown that deficiency of Cyt c can prevent appropriate apoptosome formation, inhibiting cell death and promoting cancer [7,8]. Several studies have shown that the direct external delivery of Cyt c to the cell cytosol can activate the caspase cascade and induce apoptosis in a dose-dependent manner [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A new study published in Cancer Research suggests that certain cellular mechanisms may help to explain why African American men with prostate cancer tend to develop greater therapeutic resistance and faster disease recurrence than their white counterparts . Furthermore, according to investigators, the findings could create a pathway for new therapeutic targets.…”
mentioning
confidence: 99%